تأثير تمرينات بإستخدام جهاز مقترح في تطوير سرعة الطعن و الدقة بسلاح الشيش للناشئين - عباس فاضل جابر; صباح نوري حافظ; حسام عباس ياس (physical education and sport sciences college for women/ Baghdad University, 2018)
Evolution in training to raise the level do not come only through using unfamiliar good ways in the followed traditional form so that there came the importance of research by studying the impact of exercises using proposed device in the development of Stabbing speed and accuracy with Sheesh weapon for young. And the purpose of this study is to identify the impact of exercises using proposed device in the development of Stabbing speed and accuracy with Sheesh weapon for young. for search problem crystallized through previewing some teams for young in Sheesh weapon was noted a weakness in the speed of Stabbing and precision with which necessitated that study the effect of exercise, with proposed device to develop speed of Stabbing and accuracy of Sheesh weapon for young and use experimental method of study fit for search sample consisted of 14 players of the Iraqi Federation of dual selected by intentional manner and divide by random way into two groups 7 players to the experimental group and 7 players for control group and applied the training program for two months. The study concluded that the exercises has positive impact for experimental group of research sample and recommendations on use of exercises on other age groups .